Transnational Jihadism: conflict to Be Resolved, a Movement to Implode or an Ideology to Be Countered? - Sheikh, Mona Kanwal (Perspectives on terrorism, 2022)
Over the course of two-decades-long counterterrorism campaigns in various parts of the world, al-Qaeda and—since 2014—the Islamic State have proven capable of adjusting to setbacks and surviving as transnationally operating organizations. Their continued resilience against counterterrorism efforts underscores the importance of identifying nonviolent containment strategies and furthering academic thinking on 1) resolving conflicts that involve jihadists, 2) strengthening resilience to avoid transnationalization dynamics, and 3) containing the ideological resonance of transnational jihadists. This introduction carves out the key questions that different strands of the literature on containment-related thinking have put on the contemporary research agenda. It identifies three approaches to study transnational jihadism that the contributions to this special issue illuminate further, namely studying transnational jihadism as a particular type of conflict, as a distinct form of organization, or as an ideology or theology with specific content.